Pengembangan Bahan Ajar Berbasis Pendekatan Open Ended Pada Materi FPB Dan KPK Untuk Meningkatkan Kemampuan Penalaran Siswa Di Sekolah Dasar - Eka Diana Rahmawati; Joko Sulianto; Prasena Arisyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to develop FPB and KPK teaching materials based on the Open Ended approach to improve students' reasoning abilities. This study uses the Research and Development (R & D) method with qualitative descriptive data analysis techniques. The results of the content validation in stage I obtained a value of 76.4 with a good category, in the second stage a score of 95.1 was obtained with a very good category. The results of construct validation in stage I obtained a value of 80.1 with good criteria, in stage II a value of 95.1 was obtained with very good criteria and in the results of the initial field trial of content validation a value of 94.5 was obtained with very good criteria and construct validation was obtained. 96.1 with very good criteria. In conclusion, the KPK and FPB teaching materials that have been developed through the content validation and construct validation stages can be concluded that they are valid and feasible to use to improve the reasoning abilities of students in class IV SD Gayamsari 02 Semarang.